Analisis Framing Robert N. Entman Pemberitaan Pondok Pesantren Al-Zaytun Di Media Online Kompas.com - Oktami Pangestu; Amin Shabana (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Framing is understood as the process of how someone classifies, organizes, and interprets their social experiences to understand themselves and the reality outside themselves. The current situation of radicalism raises serious concerns and needs to be watched out for. In Indonesia, radicalism is generally related to religious extremism, especially in the Islamic context. Several Islamic extremist groups in Indonesia have emerged and caused tension in society. This research aims to define the problem, estimate the source of the problem, assess morals, and emphasize solving problems that occur at the Al-Zaytun Islamic Boarding School on the online media Kompas.com. The theory used in this research is Robert N. Entman's framing analysis theory. This research uses a qualitative approach with descriptive methods. Data collection techniques use documentation and observation. Analyze data by means of data reduction, data presentation, and summary. The results of this research show the essence of the construction formed by the online media Kompas.com by looking at Robert N. Entman's dimensions, namely the selection of issues and highlighting aspects related to the selection of complex facts and realities and how the news is written. Overall, Kompas.com reports regarding the Al-Zaytun Islamic Boarding School which is affiliated with the NII at this early stage, based on the author's observations, it tends to refer more to the MUI which is struggling to be able to prove clearly and in detail to prove that the Al-Zaytun Islamic Boarding School is definitely affiliated with the NII. However, there are several things and several parties who are trying to prevent this from being revealed, but the MUI team does not want to explain this. In framing the news about the NII-affiliated Al-Zaytun Islamic Boarding School case, it emphasizes the extent to which the Al-Zaytun Islamic Boarding School case has been handled and which parties are involved in this case.